Ethanolic Extract of Moringa oleifera Leaves Reduces The Expression of ICAM-1 in Aortic Tissues of Metabolic Syndrome Induced Rattus norvegicus - Ikhsan, Muhammad Nouval; Riza novierta pesik; Dyah Ratna Budiani; Novan Adi Setyawan (Fakultas Kedokteran, Universitas Sebelas Maret, 2023)
Introduction: Metabolic syndrome poses a risk for the development of atherosclerotic lesions, which are associated with various cardiovascular diseases. Moringa leaves are known for their antioxidant and anti-inflammatory properties. ICAM-1 serves as an early marker of atherosclerosis. This study aims to investigate how the dosage of ethanolic extract from Moringa leaves affects the expression of ICAM-1 in the aortic tissue of Wistar rats with metabolic syndrome. Methods: This study employed a laboratory experimental design with a posttest only control group. The research involved 30 Wistar rats, divided into five groups: the normal control group (G1), the positive control group (G2), and three experimental groups (G3, G4, and G5). The experimental groups (G3, G4, and G5) were induced with metabolic syndrome and administered ethanolic extract of Moringa leaves at doses of 150 mg/kg, 250 mg/kg, and 350 mg/kg, respectively. The expression of aortic ICAM-1 was evaluated using the Intensity Distribution Score (IDS) and analyzed using one-way ANOVA and Post-hoc Tukey HSD test. Results: Increasing the dosage of ethanolic leaf extract of Moringa oleifera reduces the IDS value of ICAM-1 in the aortic tissue of Wistar rats with a significance of p<0.05.. Conclusion: The higher dosage of ethanolic leaf extract from Moringa oleifera Lamk has the potential to decrease ICAM-1 expression in the aortic tissue of Wistar rats with metabolic syndrome. The author hopes that Moringa leaf extract can be utilized as a supplement to prevent the formation of atherosclerotic plaques and cardiovascular diseases resulting from atherosclerotic plaques, such as thromboembolism and stroke.